2011
DOI: 10.1152/ajplung.00215.2010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulmonary arterial hypertension with circulating angiogenic cells

Abstract: Despite advances in the treatment of pulmonary arterial hypertension, a truly restorative therapy has not been achieved. Attention has been given to circulating angiogenic cells (CACs, also termed early endothelial progenitor cells) because of their ability to home to sites of vascular injury and regenerate blood vessels. We studied the efficacy of human CAC therapy in the treatment of pulmonary arterial hypertension at two different stages of disease severity. Cells were isolated from peripheral blood and adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…There is mounting interest in testing the concept that APC therapy could be important in the treatment of PH (49)(50)(51). This view is supported by observations that circulating progenitors are dysfunctional in patients with PH (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting interest in testing the concept that APC therapy could be important in the treatment of PH (49)(50)(51). This view is supported by observations that circulating progenitors are dysfunctional in patients with PH (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…[22] EPCs are thought to be important in maintaining vascular homeostasis by homing to sites of vascular injury and regenerating blood vessels. [23] In animal models and pilot studies in patients, EPC transplantation was proved to alleviate PH symptoms and pathological changes, providing a novel treatment strategy. Wang et al [6] reported that transplantation of autologous EPC can signifi cantly improve exercise capacity and pulmonary hemodynamics in PH patients.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Therapeutic effects of ex vivo expanded mature hematopoietic proangiogenic cells have mostly been studied in this model. 5,[13][14][15][16][17][18][52][53][54][55] In all but one of these studies, 56 administration of the proangiogenic cells before pulmonary hyper- tension onset decreased right ventricular systolic pressure and/or reduced remodeling. 44,52,54,55,57 One mechanism of benefit seems to be via increased expression of endothelial nitric oxide synthase (eNOS).…”
Section: Introductionmentioning
confidence: 99%